Evaluation of the Effectiveness of Mediation as an Alternative for Civil Dispute Resolution: Quantitative Research in District Courts - Kathryn, Morse; Amini, Taufiq; Kalijunjung, Kalijunjung; Pitriani, Pitriani; Lubis, Arief Fahmi (Yayasan Pendidikan Islam Daarut Thufulah, 2024)
Background. Background This research is based on the need for an effective alternative for the resolution of civil disputes in the District Court due to the problems that often arise in the conventional justice system. Mediation has been considered as one of the promising alternatives, but there has been no thorough evaluation of how effective this method is in the context of the District Court. Purpose. This study aims to quantitatively evaluate how effective mediation is as an alternative to civil dispute resolution in the District Court. Method. The quantitative method collects data through surveys and interviews with mediation participants. The aim was to determine how effective mediation is as an alternative to civil dispute resolution in the district courts. The data collected was then analyzed to identify factors that influence the success of mediation. Results. This study shows the success rate of mediation as a civil dispute resolution option in the District Court and the factors that influence the outcome. Conclusion. This study found that mediation can serve as an effective alternative to civil dispute resolution in the District Court. However, the study also emphasizes that further attention is needed to the factors that determine the success of mediation. The research also provides a basis for policy and practice recommendations that can improve the success of mediation in civil dispute resolution in the District Courts.